FACTORS THAT INTERFERE IN THE QUALITY AND QUANTITY DURING AND AFTER THE BENEFITING OF TILAPPIA (oreochromis niloticus): A REVIEW OF THE LITERATURE. (REMUNOM, 2025)
The aim of this study is to gather information on the processing of Nile tilapia (Oreochromis niloticus), with an emphasis on the requirements for using waste during and after the production process. As a highly perishable food, tilapia requires an approach that guarantees the maintenance of its quality from capture to consumption. Investigating practices and technologies that can be applied to the utilization of tilapia by-products and the maintenance of yields, investigating practices and technologies that can be applied to the utilization of tilapia by-products and the maintenance of yields. Emphasizing the importance of sustainable practices in tilapia processing, seeking alternatives that minimize waste and promote a circular economy. The information contributes to knowledge about the management of Nile tilapia, promoting efficiency and sustainability in the fishing sector and the food industry.